A review of the importance and control of Newcastle disease in Ethiopia - Dessie, Tadelle; Jobre, Y. (2004)
In this paper, available data on the distribution, economic importance and efforts made so far towards the control of Newcastle Disease (ND) in Ethiopia were presented. ND is the single major health constraint, which causes heavy mortality and morbidity to village chicken and affects productivity of the system in the country. Reviewed results, however, showed that ND in village chicken could be controlled through the use of suitable, inexpensive, locally produced and tested thermostable Australian V4 and I-2 vaccines.